Pedagogical Assessment of the Speech Activity of Modern Schoolchildren: ПЕДАГОГИЧЕСКАЯ ОЦЕНКА РАЗВИТИЯ РЕЧЕВОЙ ДЕЯТЕЛЬНОСТИ СЛАБОСЛЫШАЩИХ УЧАЩИХСЯ - Saurykova , Baglan; Abdimusa , Zhuldyz (Pedagogy and Psychology, 2025)
The study addresses the need to reconsider approaches to developing speech activity among primary school students in the modern socio-cultural context, particularly focusing on the growing pedagogical problem of students experiencing “having much knowledge without understanding” and “awareness without a speech-based foundation of comprehension.” The research examines the characteristics of speech activity development in “Literary Reading” lessons among students in inclusive education settings. Methodology and Methods. The research employs integration of theoretical-methodological and experimental-practical approaches with a focus on student personality and understanding patterns of speech development. Research methods include modified methodology by V.P. Glukhov for assessing the level of speech activity development among schoolchildren, and methodology for evaluating speech coherence by V.K. Vorobyeva and A.A. Leontiev. Pedagogical assessment involves identifying students’ abilities to perform factual and semantic analysis of communicative interaction. Results. The study identifies specific features and patterns of speech development in primary school students, establishing indicators and criteria for pedagogical assessment of speech activity. The research reveals characteristics of the speech activity development process in inclusive educational settings, providing insights into effective approaches for modern socio-cultural contexts. Scientific novelty. The research contributes to rethinking the essence and content of “speech activity of modern students,” offering innovative solutions that integrate theoretical understanding with practical application in inclusive education environments, addressing contemporary challenges in speech development. Practical significance. The findings provide educators with evidence-based approaches for developing speech activity in “Literary Reading” lessons, offering practical assessment tools and methodological guidelines that can be effectively implemented in inclusive education settings to address the identified pedagogical challenges.